Access to geological structures, density, minerals and textures through novel combination of 3D tomography, XRF and sample weight. Issue 1 (1st December 2019) - Bergqvist, Mikael; Landström, Eric; Landström, Eric; Luth, Stefan
Summary: Scanning drill cores using combined data from X-Ray Transmission and X-Ray Fluorescence, automatically measuring the weight, and performing 3D tomography of the core at the same time, gives a high-resolution 3D visualisation of the structures, textures and mineral distribution as well as elemental and density distribution along the drill hole. Data such as planar and linear structures can be annotated in the 3D volume and later exported into regional modelling or other software packages together with elemental concentrations and density. Particle sizes and distribution can be exported to produce stereo nets. An example from the European Union Horizon 2020 funded X-Mine project (2017), where a work flow is illustrated.